Genotypic and Phenotypic Characteristics of the Phylogenetic Groups of Escherichia Coli Isolates From Ostriches in Iran - Mohammad Sadegh Edalatian Dovvom; Abolfazl Ghaniei; Majid Jamshidian Mojaver; Emadodin Tohidi (The Iranian Journal of Veterinary Science and Technology)
Increased antibiotic use in the ostrich industry could lead to the emergence of virulent antibiotic-resistant bacterial strains transmissible to human. This study investigated the genotypic and phenotypic characteristics of the phylogenetic groups of Escherichia coli (E. coli) isolates from ostrich and reveal their health risk potential. One hundred twenty-nine confirmed presumptive commensal (44) and suspected pathogenic (85) E. coli isolates from ostrich flocks in Mashhad, Northeast Iran, were phylo-typed by the Clermont quadruplex polymerase chain reaction. The phylogenetic profile of the isolates was comparatively investigated based on antimicrobial susceptibility, resistance, and virulence gene profiles. Results indicated that both groups of presumptive commensal and pathogenic isolates were mostly distributed within phylogroups A (with proportions 31.81% and 32.94%, respectively) and B1 (with proportions 36.36% and 31.76%, respectively). Multi-drug resistance was highest within the phylogroup B2 (p ≥ 0.05). The phylogroup B1, typically known for commensal strains, unlike B2, showed the most negligible proportions of isolates which were devoid of resistance genes (p ≥ 0.05) and virulence genes (p ≥ 0.05). The findings of this study expanded the horizon of the genotypic and phenotypic characteristics of the phylogenetic groups of E. coli isolates from ostrich. Moreover, we indicated a complicated inconsistency between both characteristics. Therefore, more comprehensive and comparative studies on E. coli isolates from ostrich and human are favoured in future research.